2010
DOI: 10.1007/s13233-010-0714-7
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-incorporated chitosan nanoparticles based on polyelectrolyte complex formation

Abstract: Insulin-incorporated nanoparticles were prepared by polyelectrolyte complex formation using lowmolecular weight water soluble chitosan (LMWSC). Insulin-incorporated nanoparticles showed spherical shapes with a particle size of approximately 200 nm. The average particle size, drug content and loading efficiency increased with increasing insulin feed. The zeta potential decreased with increasing insulin feed, indicating that the electrostatic interaction increased with increasing insulin feed. At 1 H nuclear mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…The group concluded that the nanocomplexes of chitosandextran could be developed as simple but effective delivery system. Another study was done by Nam and coworkers where low molecular weight water soluble chitosan (LMWSC) nanocarriers were developed by the similar methods for insulin delivery (Nam et al 2010). The nanoparticles developed by the above method reported size to be approximately 200 nm.…”
Section: Polyelectrolyte Complex Methodsmentioning
confidence: 99%
“…The group concluded that the nanocomplexes of chitosandextran could be developed as simple but effective delivery system. Another study was done by Nam and coworkers where low molecular weight water soluble chitosan (LMWSC) nanocarriers were developed by the similar methods for insulin delivery (Nam et al 2010). The nanoparticles developed by the above method reported size to be approximately 200 nm.…”
Section: Polyelectrolyte Complex Methodsmentioning
confidence: 99%
“…[12][13][14] Therefore, determination of relations between independent parameters (e.g., concentration of initial materials, time of reaction, and pH) and dependent variables (e.g., size, cytotoxicity, and loading efficiency) in NPs which are made by PEC method could be very helpful in designing protein delivery systems. Effects of preparation methods, initial materials concentration, pH, temperature, and reaction time on size and loading efficiency of Cs-loaded heparin 16 and insulin 17 NPs are evaluated in 1-factor-at-a-time experimental approaches. Processing parameters (i.e., Cs concentration, pH, sonication time, and amplitude) in relation with particles' size of Cs NPs are investigated by artificial neural networks (ANNs).…”
Section: Introductionmentioning
confidence: 99%
“…[46,47]. Insulin has been successfully incorporated in chitosan nanoparticles prepared by polyelectrolyte complexation [48]. Nanoparticles prepared by cross-linking chitosan with sodium tripolyphosphate have been extensively studied.…”
Section: Applications Of Chitosan In Drug Deliverymentioning
confidence: 99%